Aktifitas Bantuan Hukum Gratis dalam Meningkatkan Akses Keadilan bagi Masyarakat Miskin - Ali Ad Dhar; Muhammad Khotami Alfarisi; Mutiara Liza; Julia Barus (Lembaga Pengembangan Kinerja Dosen, 2024)
Protection and recognition of human rights is the responsibility of the state as a consequence of its status as a country of law. Every individual, including the poor who face legal problems, has the right to receive equal treatment before the law. Access to justice is a fundamental right of every citizen, but the poor often face various obstacles in obtaining legal aid. Legal aid for the poor is guaranteed by the constitution, but its implementation still faces various obstacles. The purpose of writing this journal is to enrich the literature related to the implementation and optimization of legal aid for the poor based on Law Number 16 of 2011 concerning Legal Aid. This study uses a literature study approach by reviewing primary and secondary legal materials and analyzing them through various theories, doctrines, and legal principles. The results of this study are expected to contribute to increasing access to justice for the poor in Indonesia.